Characterization of Human-Induced Neural Stem Cells and Derivatives following Transplantation into the Central Nervous System of a Nonhuman Primate and Rats - Mengjia Li; Zhengbo Wang; Tianqi Zheng; Tianzhuang Huang; Baoguo Liu; Deqiang Han; Sumei Liu; Bochao Liu; Mo Li; Wei Si; Y. Alex Zhang; Yuyu Niu; et al. (Hindawi Limited, 2022)
Neural stem cells (NSCs) and derivatives are potential cellular sources to treat neurological diseases. In the current study, we reprogrammed human peripheral blood mononuclear cells into induced NSCs (iNSCs) and inserted GFP gene into the AAVS1 site for graft tracing. Targeted integration of GFP does not affect the proliferation and differentiation capacity of iNSCs. iNSC-GFP can be further differentiated into dopaminergic precursors (DAPs) and motor neuron precursors (MNPs), respectively. iNSCs were engrafted into the motor cortex and iNSC-DAPs into the striatum and substantia nigra (SN) of a nonhuman primate, respectively. The surviving iNSCs could respond to the microenvironment of the cortex and spontaneously differentiate into mature neurons that extended neurites. iNSC-DAPs survived well and matured into DA neurons following transplantation into the striatum and SN. iNSC-MNPs could also survive and turn into motor neurons after being engrafted into the spinal cord of rats. The results suggest that iNSCs and derivatives have a potential to be used for the treatment of neurological diseases.